2017
DOI: 10.1038/s41598-017-13301-7
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A in eggs causes development-specific liver molecular reprogramming in two generations of rainbow trout

Abstract: Bisphenol A (BPA) is widely used in the manufacture of plastics and epoxy resins and is prevalent in the aquatic environment. BPA disrupts endocrine pathways in fish, but the long-term developmental implications are unknown. We demonstrate that BPA deposition in the eggs of rainbow trout (Oncorhynchus mykiss), an ecologically and economically important species of fish, reprograms liver metabolism in the offspring and alters the developmental growth trajectory in two generations. Specifically, BPA reduces growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 59 publications
(73 reference statements)
1
25
0
1
Order By: Relevance
“…500 platform (Illumina Inc., USA) using paired-end reads v2 chemistry with 75 bp sequencing. Raw reads were trimmed and filtered using Illumina base-calling software bcl2fastq (2.14) according to published methods (Sadoul et al 2017). Alignment of reads was done using TopHat to the zebrafish genome (GRCz10/danRer10) and the abundance of the aligned counts was quantified using kallisto (Kim et al 2013).…”
Section: Rna Sequencingmentioning
confidence: 99%
“…500 platform (Illumina Inc., USA) using paired-end reads v2 chemistry with 75 bp sequencing. Raw reads were trimmed and filtered using Illumina base-calling software bcl2fastq (2.14) according to published methods (Sadoul et al 2017). Alignment of reads was done using TopHat to the zebrafish genome (GRCz10/danRer10) and the abundance of the aligned counts was quantified using kallisto (Kim et al 2013).…”
Section: Rna Sequencingmentioning
confidence: 99%
“…Body mass was periodically estimated by measuring the total mass divided by the number of fish in the tank. Growth data for BPA0, BPA3 and BPA30 treatments from both experiments were previously described in Sadoul et al (2017), whereas growth data for BPA100 were reported in Aluru et al (2010). The present study describes for the first time results for treatment BPA300.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…2 Material and methods 2.1 Long-term BPA effects on growth in rainbow trout A recent publication by Sadoul et al (2017) reported the long-term metabolic responses to BPA in eggs prior to fertilization. Reduced growth was observed in two experiments during the pre-juvenile stage followed by a sudden catch-up growth.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations